The Transition Tectonic Zone Between the Two Parts of the Platform in Iraq: A Review Study - Al-Banna, Ahmed S.; Ali, Kamal K. (Iraqi Journal of Science, 2018)
The changes of the tectonic boundary locations between the stable and unstable shelf on different version of the tectonic maps of Iraq is discussed. It is found that the location of the boundary varies due to philosophy and the type of the geological parameters. It is used the stratigraphic, geophysical, structural, geochemical, hydrological and others information in delineating the boundary. The deep crustal structures obtained by using gravity data show that the boundary shifted toward the west by about 100 km in southern Iraq. According to the review, and when taking in consideration all the geological and geophysical parameters from the lower crust to the earth surface, it is believed that the boundary is not a line but it is a tectonic crustal zone. This zone represents a transition zone between the main two regions of the platform in Iraq, and it is segmented to many subzones by transverse faults. In addition, it is believed that the data of the parameters of shallow geology confirm the eastern side of the main zone, while the lower crustal structures confirm the western side of the main zone.